(untitled) (Tạp chí Y học Cộng đồng, 2024)
Objective: To evaluate the effectiveness and safety of oral and topical tranexamic acid in the treatment of melasma. Subjects and methods: A descriptive study of a series of cases with longitudinal follow-up was conducted on 28 female patients with melasma at the Ho Chi Minh City Dermatology Hospital from April 2024 to August 2024. Results: The study subjects had an average age of 47.46 ± 8.23 (34 - 63) years old, 78.57% had a family history of melasma. The assessment of melasma improvement according to the PGA scale showed that 100% of patients had melasma improvement of over 25% (50.00% had good improvement of 51-75%). MASI index had a significant improvement after treatment compared to before treatment with statistical significance with p<0.001. All patients were satisfied after treatment with 57.14% of patients being very satisfied, 92.86% having no side effects. Conclusion: Oral and topical tranexamic acid is an effective and safe method for treating melasma.